Development of Differentiated Student Worksheets (LKPD) Oriented Towards Inquiry-Based Learning to Improve Critical Thinking Skills of High School Students on The Subject of The Human Digestive System - Vivi Kurnia Sari; Tri Jalmo; Agus Suyatna (Postgraduate, University of Mataram, 2025)
This study aims to produce differentiated student worksheets that are valid, practical, and effective in improving students' critical thinking skills. The research and development (R&D) design was conducted using the 4-D model, which consists of four steps: define, design, develop, and disseminate. The research subjects were 15 students in a small-scale trial and 66 students in a large-scale trial, all from class XI of SMA Negeri 1 Seputih Surabaya with cluster random sampling. The trial design used by the researcher was a non-equivalent control group design. The instruments used were needs analysis questionnaires, validity questionnaires, practicality questionnaires, learning implementation observation sheets, and pretest-posttest of critical thinking skills. Data analysis techniques for validity and practicality use descriptive percentage analysis, while data analysis for effectiveness uses statistical analysis (independent sample t-test, paired sample t-test and one-way anova). The results of the development research indicate that differentiated student worksheets are highly valid (94%); differentiated student worksheets are practical for improving students' critical thinking skills in terms of learning implementation; differentiated student worksheets were effective in improving students' critical thinking skills with a large effect size (0.99). The conclusion is that differentiated worksheets on the human digestive system have been developed that can improve students' critical thinking skills.